Interactions in water-energy-food security nexus: A case study of South Korea - An, Daehan (Frontiers in Water, 2022)
With the exponential increase in the demand for water, energy, and food (WEF), WEF security is being threatened. To address this issue, the nexus approach, which explores interactions among different WEF sectors as an integrated system, can distinguish between different influencing indicators of WEF security. However, studies on the interactions between WEF sectors in South Korea are few, consequently challenging WEF security, and in the field of social science, WEF security nexus research using a quantitative approach is lacking. This study discusses the interactions composed of synergies and trade-offs between WEF sectors in South Korea through Spearman’s rank correlation and network analyses using secondary data at the national level. The results show that the interaction between energy or energy-related sectors was highest; specifically, increasing the proportion of renewable energy utilization improved WEF security. In the water and food sectors, water infrastructure management and value-added management of agriculture showed the most interactions, respectively. The findings demonstrate that WEF security is an interconnected rather than an independent system, and WEF security improves efficiently when preferentially upgrading indicators with many interactions. The study provides important guidelines to prioritize policies to implement sustainable resource management systems.